Dose-Dependent Effects of Snakehead Fish (Channa Striata) Oil Extract on Lipid Profile and Inflammatory Markers in Diet-Induced Dyslipidemic Rats - Gratify Ayu Dwi Anjani; Titiek Sumarawati; Chodijah Chodijah (Media of Health Research, 2026)
Dyslipidemia is a major cardiovascular risk factor closely associated with chronic inflammation. Snakehead fish (Channa striata) contains omega-3 fatty acids and bioactive peptides with lipid-modulating and anti-inflammatory potential. However, its dose-dependent effects on lipid and inflammatory parameters remain unclear. This study investigated the dose-dependent effects of C. striata oil extract on lipid profile and inflammatory markers in diet-induced dyslipidemic rats. Twenty-four male Wistar rats were randomized into four groups (n=6): normal control, dyslipidemia model, low-dose extract (150 mg/kgBW), and high-dose extract (250 mg/kgBW). Dyslipidemia was induced using quail egg yolk (4 mL/kgBW/day) for 14 days, while treatments were administered orally. Serum LDL, HDL, TNF-α, and IL-10 levels were analyzed using spectrophotometry and ELISA. Dyslipidemia induction significantly increased LDL and TNF-α and reduced HDL and IL-10 (p<0.001). Both extract doses improved all parameters, with the 250 mg/kgBW dose producing the strongest effects: LDL reduction of 55%, HDL restoration to 76% of control, TNF-α reduction of 64%, and IL-10 elevation to 74% of control. These findings demonstrate clear dose-response effects. C. striata oil extract exhibits significant anti-dyslipidemic and anti-inflammatory properties, supporting its potential as a natural adjunct therapy for dyslipidemia management.